Rational design of inducible CRISPR guide RNAs for de novo assembly of transcriptional programs - Quentin R. V. Ferry (Nature Portfolio, 2017)
Being able to regulate gene expression in a controllable manner is one of the promises of synthetic biology, and CRISPR-Cas9 is one of the tools being developed to achieve that goal. Here the authors develop an inducible CRISPR platform using an engineered guide RNA.